FIRST-ORDER SYMMETRY OF WEAK-FIELD PARTIAL THERMOREMANENCE IN MULTI-DOMAIN (MD) FERROMAGNETIC GRAINS: 2. IMPLICATIONS FOR THELLIER-TYPE PALAEOINTENSITY DETERMINATION - Biggin A.J. (My University, 2006)
Two models, derived in very different ways but both incorporating the symmetry constraints outlined in the previous paper, are developed for use in simulating Thellier-type palaeointensity experiments. These are then tested against experimental data which endorse them both as powerful tools. They predict that non-ideal behaviour due to MD grain content is sensitive not only to the protocol employed and the vector difference between the partial thermoremanent magnetisations (pTRMs) imparted in the laboratory and the natural remanent magnetisation (NRM), but also to the spacing of the temperature steps and the type of pTRM imparted during the remagnetisation stages. Consistent with experimental studies, the models predict that pTRM checks may fail despite no alteration occurring and that any double-stage experimental protocol will produce non-ideal results to some degree provided that MD grains are present. A single-heating (perpendicular or high-angle single heating) protocol is predicted to remove non-ideal effects provided that the grains obey the symmetry constraints perfectly. However, this remains to be experimentally tested and does not allow for the use of pTRM checks. Five straightforward recommendations for future palaeointensity studies to follow are outlined. These are designed to minimise non-ideal behaviour due to MD grains as far as possible while retaining the capacity to detect and reject those samples which will nonetheless produce significant errors. © 2006 Elsevier B.V. All rights reserved.
Keywords: MULTIDOMAIN GRAINS; PALAEOMAGNETISM; THELLIER PALAEOINTENSITY DETERMINATION; THERMOREMANENT MAGNETISATION